Extensive winter subglacial water storage beneath the Greenland Ice Sheet. Issue 24 (29th December 2016) - Chu, Winnie; Schroeder, Dustin M.; Seroussi, Helene; Creyts, Timothy T.; Palmer, Steven J.; Bell, Robin E.
Abstract: Surface meltwater that reaches the base of the Greenland Ice Sheet exerts a fundamental impact on ice flow, but observations of catchment‐wide movement and distribution of subglacial water remain limited. Using radar‐sounding data from two seasons, we identify the seasonal distribution of subglacial water in western Greenland. Our analysis provides evidence of widespread subglacial water storage beneath Greenland in the wintertime. The winter storage is located primarily on bedrock ridges with higher bed elevations in excess of 200 m. During the melt season water moves to the subglacial troughs. This inverse relationship with topography indicates that the material properties of the glacier bed strongly influence subglacial drainage development. Both the spatial variations in bed properties and the initial state of the subglacial hydrology system at the start of the melt season lead to differing glacier dynamical responses to surface melting across the Greenland Ice Sheet. Key Points: Radar reflectivity shows extensive wintertime subglacial water storage primarily on basal ridges in Greenland In the summertime, reflectivity data show that the drainage pattern changes with deep troughs conduct water when the ridges drain Seasonal changes in subglacial drainage distribution are controlled by the material properties of the glacier bed